HIV escape mutations occur preferentially at HLA-binding sites of CD8 T-cell epitopes - Bronke, Corine; Almeida, Coral-Ann M.; McKinnon, Elizabeth; Roberts, Steven G.; Keane, Niamh M.; Chopra, Abha; Carlson, Jonathan M.; Heckerman, David; Mallal, Simon; John, Mina (AIDS, Basic Science, 2013)
Objective: To define the relative frequencies of different mechanisms of viral escape. Design: A population-based approach to examine the distribution of HIV polymorphism associated with diverse population human leucocyte antigens (HLAs) at sites within and flanking CD8 T-cell epitopes as a correlate of likely mechanisms of viral escape. Methods: Sequence windows surrounding 874 HLA allele-specific polymorphisms across the full HIV-1 proteomic consensus sequence were scanned by an epitope-prediction programme. Either already known or probable CD8 T-cell epitopes with HLA restriction matching that of the proximal HLA association were identified and synthesized. These peptides were used as stimulating antigens in automated enzyme-linked immunospot (ELISpot) assays. Peptide arrays were customized to each individual based on their HLA genotype. Results: Among HLA-associated HIV polymorphisms detected in the viral sequences of a cohort of 800 individuals with chronic subtype B HIV infection, those which were likely to affect HLA peptide binding were significantly more common than polymorphisms at nonanchor HLA binding sites. HIV epitopes with such polymorphisms were associated with reduced IFNγ responses in ELISpot assays. HIV escape at sites affecting T-cell receptor (TCR) engagement and epitope processing were also evident. Conclusion: HIV escape from HLA-peptide binding predominates as an effective viral evasion strategy and therefore has implications for inclusion of HLA-adapted epitopes in vaccine immunogens.